Comparação entre a efetividade da interface helmet usando fluxometros versus ventilador mecânico para ventilação não invasiva em pacientes com COVID-19: ensaio clínico controlado e randomizado - Ferreira, Fernanda dos Reis (2022)
Background: The severe acute respiratory distress syndrome coronavirus 2 (SARS-CoV-2) has as its main clinical manifestation the acute hypoxemic respiratory failure, which in 58% of cases of patients admitted to intensive care units (ICUs) evolves with the need for invasive mechanical ventilation (IMV). Non-invasive ventilation (NIV) using the helmet interface is an alternative to reduce intubation and mortality rates. With the shortage of mechanical ventilator (MV) during the peak periods of the pandemic, the use of the helmet interface pressurized with oxygen flow meter (FM) and PEEP valve (PV) was an important alternative for the application of NIV in these patients. Objective: To compare the effectiveness of helmet interface with FM and PV versus the MV in performing NIV in patients with SARS-CoV-2. Method: This single-center randomized clinical trial recruited a total of 135 adult subjects in a private hospital designed for the treatment of patients diagnosed with SARS-CoV-2. Patients were randomized into two groups: (a) intervention group (IG), who wore the helmet with FM and PV; and (b) control group (CG), that pressurized using MV. They followed a protocol for inclusion, evaluation of blood gases, respiratory rate (RR), peripheral oxygen saturation (SpO2), modified Borg scale, and a visual analog scale. Results: The mean intubation rates for the CG and IG were 56.1 and 42.6 %, respectively, without a statistical difference (P=0.27). The average number of days of helmet use for the IG were 3.9 (± 2.7) and 4.3 (± 4.7) for the CG. The mean number of hospitalizations in the IG were 16.0 (±7.7) vs. 18.1 (9.6) from the CG. Conclusion: As a relevant point of this study, we highlight that this is the first study to show that pressurizing the helmet interface using an OF and a PV is as effective as a MV. This enables a low-cost therapeutic alternative.